(untitled) (Journal of Surgical Sciences, 2020)
Background: Modern surgical techniques and improved preoperative care has reduced both morbidity and mortality of colorectal surgery but the role of mechanical bowel preparation is recently disputed. Primary colonic anastomosis without mechanical bowel preparation is still considered unsafe. Objective: One of the objectives of this study was to evaluate pre-operative mechanical bowel preparation in preventing anastomotic and wound dehiscence in elective colon and rectal surgery. Methods: Fifty patients who were included in this study were randomly divided into two groups (group A & Group B). Group A was the preparatory group and Group B was the non-preparatory group. In preparatory group oral poly ethylene glycol was used for mechanical bowel preparation and in non-preparatory group no bowel preparation done. All patients were operated on by qualified surgeons and followed up for outcome and collected data were analyzed. Results: 80% of the Patients in Group A had adverse effects of bowel preparation like nausea, vomiting, blotting, loose motion and precaution had to be taken for them. All the patients of both groups were given per-operative antibiotics whereas 24 patients of Group A and 23 patients of Group B were given transfusion. 15(60%) patients of Group A had developed post-operative surgical infectious complications. The majority number of patients of Group A had been suffered from surgical site infection (10, 40%) followed by Anastomotic Leak, Intra-abdominal abscess and Peritonitis whereas in Group B 10(40%) patients developed surgical complications. Conclusion: Mechanical bowel preparation before elective colon and rectal surgery is not so effective in preventing complications and without any mechanical preparation of the bowel colorectal surgery can be done safely. Journal of Surgical Sciences (2017) Vol. 21 (2): 105-109